2013
DOI: 10.1371/journal.pone.0060111
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Retinoid Acid Receptor-Related Orphan Receptor Alpha (RORA) and Neuropeptide S Receptor 1 (NPSR1) in Asthma

Abstract: Retinoid acid receptor-related Orphan Receptor Alpha (RORA) was recently identified as a susceptibility gene for asthma in a genome-wide association study. To investigate the impact of RORA on asthma susceptibility, we performed a genetic association study between RORA single nucleotide polymorphisms (SNPs) in the vicinity of the asthma-associated SNP (rs11071559) and asthma-related traits. Because the regulatory region of a previously implicated asthma susceptibility gene, Neuropeptide S receptor 1 (NPSR1), h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(44 citation statements)
references
References 66 publications
(71 reference statements)
3
38
2
Order By: Relevance
“…The children were examined and blood samples were taken at 4 and/or 8 y of age. DNA was available from 2033 subjects collected at 8 y of age (33). Subjects diagnosed with asthma at any follow-up from 1 to 16 y were considered as asthma cases (n = 440, of which 300 are also allergy cases) and healthy, nonasthmatic, nonallergic as controls (n = 839).…”
Section: Bamse Samplesmentioning
confidence: 99%
“…The children were examined and blood samples were taken at 4 and/or 8 y of age. DNA was available from 2033 subjects collected at 8 y of age (33). Subjects diagnosed with asthma at any follow-up from 1 to 16 y were considered as asthma cases (n = 440, of which 300 are also allergy cases) and healthy, nonasthmatic, nonallergic as controls (n = 839).…”
Section: Bamse Samplesmentioning
confidence: 99%
“…Furthermore, polymorphism in NPSR1 was associated with bedtime and sleepiness in a genome-wide association study [48]. Motivated by these findings, we previously showed that NPS affects circadian clock gene expression in the same SH-SY5Y cell line with NPSR1 overexpression [35]. Of these genes that regulate circadian molecular clock machinery, NPAS2 , PER1 , CRY1 , and RORA were among the most affected genes in the current microarray experiment.…”
Section: Discussionmentioning
confidence: 71%
“…After 24 h, the cells were transfected with recombinant full-length NPSR1 constructs fused with either red fluorescence protein (NPSR1-A-pDsRed) or green fluorescent protein (NPSR1-B-GFP) using 1.3 μl Fugene HD and 0.5 μg of DNA per well. Construction of the expression vectors has been described earlier [35]. After 24 h, the cells were fixed with 4 % paraformaldehyde in phosphate-buffered saline (PBS) for 5 min.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, ignoring epistatic effects may mask important genetic susceptibility. While other studies have utilized biologic plausibility 51, 52 , results from linkage analyses 53, 54 and bioinformatics 54, 55 to inform analyses of genetic interactions in asthma, our study is the first to apply this approach in an independent population and replicate findings where no significant independent effects were observed (blacks).…”
Section: Discussionmentioning
confidence: 91%